Peranan Teknologi dalam Peningkatan Mutu Pendidikan Pembelajaran Bahasa di SMAN 1 Katingan Hulu Kabupaten Katingan - Ni Putu Eka Merliana; Ni Nyoman Tantri; Evie; Winawati (UHN IGB Sugriwa Denpasar, 2019)
Technology becomes a thing that has an influence on the life needs of society as a whole, both to fulfill economic, social, cultural and educational needs. One of the things that is concerned by the government at this time is the progress of the quality of education which is the basis for educating the Indonesian people as a whole. The breakthrough made by the government to improve the quality of education is to implement a curriculum based learning system (K-13) in which students both at the elementary school level, junior high school and high school must be creative and innovative in implementing learning in the classroom. The application of this curriculum cannot be separated from the use of technology where teachers and students can develop dynamic and fun learning. One of the subjects offered in K-13 learning is language learning where these subjects become the foundation of students to carry out communication and interaction everyday. Therefore, the aim of the study is to know how to improve quality in language learning in SMAN-1 Katingan Hulu, Katingan Regency.